Statistics in quality improvement: Measurement and statistical process control. Issue 5 (4th March 2021) - Wolfe, Heather A.; Taylor, April; Subramanyam, Rajeev
Abstract: Data are used in healthcare quality improvement endeavors to measure and determine whether the changes made in the course of the work have made the desired impact. The methods used to analyze data in quality improvement differ slightly from those used in classical statistics. Run charts and statistical process control charts are the most common types of graphical representations used to visualize data collected for quality improvement. This review provides a basic introduction to measurement in quality improvement and explains the use of run charts and statistical process control charts with real‐life examples.